Molecular Nodal Restaging Based on CEACAM5, FGFR2b and PTPN11 Expression Adds No Relevant Clinical Information in Resected Non-Small Cell Lung Cancer. Issue 2 (1st February 2022) - Macia, Ivan; Aiza, Gemma; Ramos, Ricard; Escobar, Ignacio; Rivas, Francisco; Ureña, Anna; Aso, Samantha; Rosado, Gabriela; Rodriguez-Taboada, Pau; Deniz, Carlos; Nadal, Ernest; Capella, Gabriel
Abstract: Background: The relapse rate in non-small cell lung cancer (NSCLC) is high, even in localized disease, suggesting that the current approach to pathological staging is insufficiently sensitive to detect occult micrometastases present in resected lymph nodes. Therefore, we aimed to determine the prognostic value of the expression of embryonic molecular markers in histologically-negative lymph nodes of completely-resected NSCLC. Methods: 76 completely-resected NSCLC patients were included: 60 pN0 and 16 pN1. Primary tumors and 347 lymph node were studied. CEACAM5, FGFR2b, and PTPN11 expression levels were evaluated through mRNA analysis using real-time RT-qPCR assay. Statistical analyses included the Kruskal-Wallis test, Kaplan Meier curves, and log-rank tests. Results: CEACAM5 expression levels were scored as high in of 90 lymph nodes (26%). The molecular-positive lymph nodes lead to the restaging of 37 (62%) pN0 patients as molecular N1 or N2 and 5 (31%) pN1 cases were reclassified as molecular-positive N2. Surprisingly, molecular-positive patients associated with a better OS (overall survival, p = 0, 04). FGFR2b overexpression was observed in 41 (12%) lymph nodes leading to the restaging of 17 patients (22%). Again a trend was observed toward a better DFS (disease-free survival) in the restaged patients (p = 0, 09). Accordingly, high expression levels of CEACAM5 or FGFR2b in the primary were related to better DFS (p = 0, 06; p < 0, 02, respectively). Conclusion: Molecular nodal restaging based on expression levels of CEACAM5 and/or FGFR2b, does not add relevant clinical information to pathological staging of NSCLC likely related to the better prognosis of their overexpression in primary tumors.